Uncovering metacognitive awareness and meaningful learning of prospective mathematics teachers after learning absolute value inequalities - Wayan Rumite; Halil Arianto; Syamsinar Syamsinar (Universitas Muhammadiyah Surakarta, 2026)
Learners who lack adequate metacognitive awareness and meaningful have the potential to work mechanically. The aims of this study is to uncover the characteristics and description of metacognitive awareness and meaningful of prospective mathematics teachers after learning absolute value inequalities and the involvement of intuitive and analytical thinking. This study uses a qualitative approach with an exploratory type. A total of 5 prospective mathematics teachers who were taking differential calculus courses were selected as subjects from 87 candidate subjects from two different universities in Indonesia. Data collection was carried out by administering tests and conducting semi-structured interviews. Data analysis in this study went through three stages, namely data reduction, data presentation, and drawing conclusions. The results of data analysis show that: 1) unaware and not meaningful, 2) aware but not meaningful, 3) unaware but meaningful, 4) aware and meaningful. In addition, a pattern of intuitive and analytical thinking was also found, whereby prospective mathematics teachers who were not conscious activated analytical thinking, while those who were conscious activated intuitive thinking. These findings imply the importance of emphasizing mindful and meaningful during the learning process so that students can understand concepts holistically and deeply, enabling them to solve problems accurately.